Latest Findings from Randomized Evaluations of Microfinance - Bauchet, Jonathan (World Bank, Washington, DC, 2017)
This paper summarizes the latest research findings from a new body of empirical evidence that uses randomized evaluations, similar to those used in medical trials, to compare how one group responds to access to specific new financial services against how a comparable group fares without those services. This paper goes back a couple of years to the first studies that used this approach, and summarizes a series of research studies presented at the October 2010 microfinance impact and innovation conference in New York. These studies evaluated product design for a range of financial services, including credit, savings, and insurance. The studies discussed here were undertaken by research affiliates of Innovations for Poverty Action (IPA), the Financial Access Initiative (FAI), and the Abdul Latif Jameel Poverty Action Lab (J-PAL) at the Massachusetts Institute of Technology; they are all randomized evaluations unless otherwise specified. Part one of this paper reviews the main results from randomized evaluations that measure the impact of microcredit and micro savings on business investment and creation, consumption, and household well-being. Part two presents evidence from evaluations of products and delivery design. Part three discusses the evidence on micro insurance products.